Identification of common fungal extracellular membrane (CFEM) proteins in Fusarium sacchari that inhibit plant immunity and contribute to virulence - Zhen Huang; Yuming Zhou; Huixue Li; Yixue Bao; Zhenzhen Duan; Caixia Wang; Charles A. Powell; Kai Wang; Qin Hu; Baoshan Chen; Jisen Zhang; Muqing Zhang; et al. (Microbiology Spectrum, 2023)
ABSTRACT Fusarium sacchari is one of the primary pathogens causing pokkah boeng disease in sugarcane in China. Common fungal extracellular membrane (CFEM) domain-containing proteins only exist in fungi and play a significant role in the interaction of pathogens and plants. However, the CFEM proteins in F. sacchari were not identified and functionally resolved. Of the 20 FsCFEM proteins identified from the genome of F. sacchari, 16 FsCFEM genes were cloned, while 4 FsCFEM proteins (Fs06761, Fs08184, Fs10706, and Fs13617) were identified as effector proteins that could suppress the programmed cell death triggered by BCL2-associated X protein in Nicotiana benthamiana. Subcellular localization analysis revealed that these four effectors could enter plant cells and are mainly located in the cell membrane and nucleus. By the yeast YTK12 secretion system, the signal peptides of four CFEM proteins were functionally verified. The expression levels of these four effector proteins were significantly increased in the F. sacchari-infected sugarcane plants. Through fungal gene knockout, three genes (Fs06761, Fs08184, and Fs13617) were found to be important pathogenic factors for pathogens. Our results support that the FsCFEM effector proteins were virulence effectors and might be involved in regulating plant immunity. IMPORTANCE Common fungal extracellular membrane (CFEM) domain-containing protein has long been considered an essential effector, playing a crucial role in the interaction of pathogens and plant. Strategies aimed at understanding the pathogenicity mechanism of F. sacchari are eagerly anticipated to ultimately end the spread of pokkah boeng disease. Twenty FsCFEM proteins in the genome of F. sacchari have been identified, and four FsCFEM effector proteins have been found to suppress BCL2-associated X protein-triggered programmed cell death in N. benthamiana. These four effector proteins have the ability to enter plant cells and inhibit plant immunity. Furthermore, the expression of these four FsCFEM effector proteins significantly increases during the infection stage, with the three of them playing an essential role in achieving full virulence. These study findings provide a direction toward further exploration of the immune response in sugarcane. By applying these discoveries, we can potentially control the spread of disease through techniques such as host-induced gene silencing.